PENERAPAN FRAMEWORK COBIT 4.1 DAN BSC PADA AUDIT SISTEM INFORMASI INSTLASI RAWAT INAP RUMAH SAKIT - Hasan, Patmawati; Pawan, Elvis; Y. Bei, Sariaty H.; M. H. Thamrin, Rosiyati (Informasi Interaktif, 2020)
Management Information System (SIM-RS) that controls the information system in the inpatient unit. This system is used to handle customers as well as collaboration with third party vendors. There are business processes, such as patient registration, service to patients, patient medical records and details of patient treatment costs. Hospital business processes require different information and specific patient data. The patient information and data provide opportunities for other business functions in the hospital to carry out certain processes. For this reason, Bhayangkara Kindergarten Hospital. III Jayapura applies information technology in its operations.To measure the alignment between business processes, applications, and business strategies, it is necessary to conduct an audit of existing information systems. Audits are conducted using the COBIT 4.1 standard and applying the Balanced Scorecard to the customer's perspective.In this research, the Maturity Level 2.55 value is generated, which is included in the repeatable but intuitive category. The study provides recommendations for improving the information system process in the form of standardization of existing procedures.Â Keywords:Â  Cobit 4.1, BSC, Rumah Sakit